2020
DOI: 10.4414/smw.2020.20392
|View full text |Cite
|
Sign up to set email alerts
|

The Swiss STAR trial – an evaluation of target groups for sexually transmitted infection screening in the sub-sample of men

Abstract: OBJECTIVES: In Switzerland, universal health insurance does not cover any routine testing for sexually transmitted infections (STIs), not even in individuals at high risk, and extra-genital swabbing is not standard of care. We determined the prevalence and incidence of human immunodeficiency virus (HIV), viral hepatitis and non-viral STIs in a multicentre prospective observational cohort of multi-partner men who have sex with men (MSM) and other men.MATERIALS AND METHODS: Between January 2016 and June 2017, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
0
16
1
1
Order By: Relevance
“…Of note, in the SHCS, syphilis is screened for routinely every 1–2 years irrespective of symptoms, which might contribute to the high syphilis incidence in this study compared with other STIs. In a recent survey among asymptomatic MSM with at least 3 sexual partners attending voluntary counseling and testing (VCT) sites in Switzerland, the incidence for syphilis was 42/1000 PYFU, the incidence for gonorrhoea was 147/1000 PYFU, and the incidence for was chlamydia 90/1000 PYFU [ 13 ]. Of note, in this VCT sites study, only 3.6% of the participants had a diagnosed HIV infection at the time of enrollment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, in the SHCS, syphilis is screened for routinely every 1–2 years irrespective of symptoms, which might contribute to the high syphilis incidence in this study compared with other STIs. In a recent survey among asymptomatic MSM with at least 3 sexual partners attending voluntary counseling and testing (VCT) sites in Switzerland, the incidence for syphilis was 42/1000 PYFU, the incidence for gonorrhoea was 147/1000 PYFU, and the incidence for was chlamydia 90/1000 PYFU [ 13 ]. Of note, in this VCT sites study, only 3.6% of the participants had a diagnosed HIV infection at the time of enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there might be an underestimation of the overall cases if patients did not report all STIs diagnosed in external settings, including VCT sites, or missed to report specific symptoms. Of note, among people attending a VCT site, 3.8% were already known to be HIV positive [ 13 ]. However, in this context, it is important to optimize screening strategies according to clinical and behavioral characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some countries, therefore, explicitly recommend biannual syphilis-screening in multi-partners MSM. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, these studies included symptomatic MSM or partners of individuals with confirmed Neisseria gonorrhoeae or Chlamydia trachomatis infections, whereas our study participants were exclusively asymptomatic patients, which may account for our different findings. Specimen pooling has been used to determine prevalence of Mycoplasma genitalium infection in both male and female patients 15,16 ; however, to our knowledge, there are no prior studies evaluating whether performance of the assay itself is affected by pooling of samples from multiple sites. Although routine M. genitalium screening is not recommended by the CDC due to a limited knowledge on the effects of asymptomatic infections, 7 epidemiological studies may help define specific patient populations for future research follow-up.…”
Section: Discussionmentioning
confidence: 99%